PEMETAAN PERSEBARAN PENDERITA DEMAM BERDARAH DENGUE MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KABUPATEN BANTUL TAHUN 2024 - Andhy Sulistyo (RAGAM: Journal of Statistics & Its Application, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem with fluctuating incidence in Indonesia, including Bantul District. In 2024, 672 DHF cases were reported, a sharp increase compared to 135 cases in the previous year. This situation highlights the need for spatial analysis to better understand the disease distribution and support effective control strategies. This study aims to map the distribution of DHF cases in Bantul District in 2024 and analyze spatial patterns using Geographic Information Systems (GIS). A descriptive quantitative study with a case study approach was conducted. The population consisted of all reported DHF cases in 2024 obtained from the Bantul District Health Office, including patient residential coordinates. Spatial analysis was performed using ArcGIS 10.3. Global Moran’s I was applied to assess spatial autocorrelation, the Average Nearest Neighbor (ANN) method was used to determine distribution patterns, and the Central Feature tool identified the central point of case concentration. The analysis revealed that DHF cases were significantly clustered, as indicated by a positive Moran’s I value (p<0.05) and an ANN index <1. The central feature analysis showed that case concentrations were mainly located in the working areas of Pleret and Imogiri II primary health centers. The distribution of DHF cases in Bantul District in 2024 is not random but clustered in specific areas. These findings provide crucial evidence for prioritizing targeted interventions such as fogging, community education, and more focused source reduction programs.